TREAT eDelphi exercise for AE photo‐ and systemic therapy registries. (1st April 2019) - Gerbens, L.A.A.; Apfelbacher, C.J.; Irvine, A.D.; Barbarot, S.; de Booij, R.J.; Boyce, A.E.; Deleuran, M.; Eichenfield, L.F.; Hof, M.H.; Middelkamp‐Hup, M.A.; Roberts, A.; Schmitt, J.; et al.
Summary: Atopic eczema (AE) is sometimes severe enough to need strong medicines, but there is not much information available to help doctors select the right treatment. Published trials of different drugs are difficult to assess because they include carefully selected patients and measure responses in different ways. Data from patients actually using these drugs outside of research trials, collected in a registry, could provide a much better picture of long‐term, real‐life experience, but only if everyone reports their observations in the same terms ("outcome measures"). In this study the international TREatment of ATopic eczema (TREAT) Registry Taskforce conducted an online exercise to agree a minimum set of variables that should be measured and reported to AE registries. An initial list of 119 possible items was sent to 479 participants in 36 countries: mostly doctors but also nurses, researchers, patients, industry and regulatory body representatives; 86% responded, rating each item from 0 (not important) to 9 (critical). The list was whittled down through two further rounds; after each round, a summary of the responses was fed back and participants were invited to either keep or change their original answers. Finally, 42 participants attended a consensus meeting and agreed a core set of 49 baseline items and 20 follow‐up items. Hopefully standardising outcome measures in future trials will fill the current gaps of evidence and improve the care of people with AE. However, as the accompanying editorial points out, agreeing outcome measures is only one of many challenges in developing effective registries.